Normothermic ex situ machine perfusion of vascularized composite allografts with oxygen microcarriers for 12 hours using real-time mitochondrial redox quantification - Haug, Valentin; Peng, Yifeng; Tchiloemba, Bianief; Wang, Alice T.; Buerger, Florian; Romfh, Padraic; Kneser, Ulrich; Polizzotti, Brian D.; Pomahac, Bohdan (Journal of Clinical Medicine, 2023)
Background: Normothermic ex situ perfusion of vascularized composite allografts (VCAs) necessitates high oxygen demand and, thus, increased metabolic activity, which, in turn, requires the use of blood-based perfusion solutions. However, blood-derived perfusates, in turn, constitute an antigenic load. To circumvent this immunogenic problem, we used a perfusate enriched with acellular dextrane oxygen microcarriers to perfuse rat hindlimbs. Methods: Rat hindlimbs (n = 11) were perfused with either (non-), oxygenated dextrane-enriched Phoxilium, or Phoxilium enriched with dextrane oxygen microcarriers (MO2) for 12 h at 37 °C or stored on ice. Oxygenation of the skeletal muscle was assessed with Raman spectroscopy, tissue pO2-probes, and analysis of the perfusate. Transmission electronic microscopy was utilized to assess the ultrastructure of mitochondria of the skeletal muscle. Results: For all evaluated conditions, ischemia time until perfusion was comparable (22.91 ± 1.64 min; p = 0.1559). After 12 h, limb weight increased significantly by at least 81%, up to 124% in the perfusion groups, and by 27% in the static cold storage (SCS) group. Raman spectroscopy signals of skeletal muscle did not differ substantially among the groups during either perfusion or static cold storage across the duration of the experiment. While the total number of skeletal muscle mitochondria decreased significantly compared to baseline, mitochondrial diameter increased in the perfusion groups and the static cold storage group. Conclusion: The use of oxygen microcarriers in ex situ perfusion of VCA with acellular perfusates under normothermic conditions for 12 h facilitates the maintenance of mitochondrial structure, as well as a subsequent recovery of mitochondrial redox status over time, while markers of muscle injury were lower compared to conventional oxygenated acellular perfusates.